The Rise of Prussian Blue Analogs: Challenges and Opportunities for High‐Performance Cathode Materials in Potassium‐Ion Batteries. Issue 1 (9th October 2020) - Zhao, Shuoqing; Guo, Ziqi; Yan, Kang; Guo, Xin; Wan, Shuwei; He, Fengrong; Sun, Bing; Wang, Guoxiu
Abstract : Potassium‐ion batteries (PIBs) are emerging as one of the potential alternatives to lithium‐ion batteries for next‐generation rechargeable battery systems. Nevertheless, the lack of suitable cathode materials with high capacity hinders their practical applications. Recently, Prussian blue analogs (PBAs) cathode materials stand out as promising candidates for PIBs. Their unique crystal structure with open 3D frameworks and large interstitial voids favors fast K + intercalation without causing drastic volume expansion, which is the prerequisite for high‐rate and long‐term battery operation. Herein, a fundamental review on the development and advance of PBAs cathode materials is presented for PIBs with in‐depth elucidation of their crystal structures, chemical compositions, and electrochemical performances. Particularly, the unique and prominent advantages of PBAs in both aqueous and nonaqueous PIBs are highlighted. In addition, to bridge the current gap from the laboratory to future commercialization, potential improvement strategies are proposed to overcome the present drawbacks. Finally, perspectives and new insights are provided for further exploration and research in PBAs for better PIBs. Abstract : By investigating the correlation among the structure, chemical composition and redox reaction mechanisms, recent advances in Prussian blue analogs as cathode materials for non‐aqueous and aqueous potassium‐ion batteries are reviewed and summarized. Meanwhile, improvement strategies to overcome technical hurdles are also concluded and discussed. Finally, perspectives and outlook for the future development of Prussian blue analogs are provided.